2015
DOI: 10.1107/s1600577515005937
|View full text |Cite
|
Sign up to set email alerts
|

The Extreme Conditions Beamline P02.2 and the Extreme Conditions Science Infrastructure at PETRA III

Abstract: Performance description of the Extreme Conditions Beamline (ECB, P02.2) at PETRA III that is optimized for micro-diffraction at simultaneous high pressure and high and low temperatures created in different diamond anvil cells environments. Additional information of the capabilities of the Extreme Conditions Science Infrastructure for DAC work is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
137
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(148 citation statements)
references
References 54 publications
0
137
0
Order By: Relevance
“…The laser power of the system was kept below 3 mW to prevent back transformation of the HI sample to I 2 and H 2 and laser exposure minimized to 0.2 s. We have found that above 1-2 GPa, photodissociation of I 2 is not possible with 200 mW of 532 nm laser light. X-ray diffraction data were collected at beam lines BL10XU, SPring-8, Japan and P02.2 ECB, PETRA, Germany [22,23]. Angle-dispersive x-ray diffraction patterns were recorded on PerkinElmer XRD1621 and Marr345 image-plate detectors with microfocused synchrotron radiation sources with energies in the range 30-43 keV.…”
Section: Methodsmentioning
confidence: 99%
“…The laser power of the system was kept below 3 mW to prevent back transformation of the HI sample to I 2 and H 2 and laser exposure minimized to 0.2 s. We have found that above 1-2 GPa, photodissociation of I 2 is not possible with 200 mW of 532 nm laser light. X-ray diffraction data were collected at beam lines BL10XU, SPring-8, Japan and P02.2 ECB, PETRA, Germany [22,23]. Angle-dispersive x-ray diffraction patterns were recorded on PerkinElmer XRD1621 and Marr345 image-plate detectors with microfocused synchrotron radiation sources with energies in the range 30-43 keV.…”
Section: Methodsmentioning
confidence: 99%
“…Single crystals of β-B in a DAC were studied on ID27 at the European Synchrotron Radiation Facility (ESRF) and on P02.2 at PETRA III, DESY [27].…”
Section: Methodsmentioning
confidence: 99%
“…The ruby luminescence method was used for measuring pressure. 24 Angle-resolved high-pressure powder XRD measurements were performed at the Extreme Conditions Beamline P02.2 of PETRA III (Hamburg, Germany) 25 with an incident X-ray wavelength k ¼ 0.289 Å and a beam size of 2 lm  2 lm. Two-dimensional XRD patterns were collected with a fast flat panel detector XRD1621 from PerkinElmer (2048 pixels  2048 pixels, 200  200 lm 2 pixel size) and processed with the FIT2D software.…”
mentioning
confidence: 99%